Cross-sectional and longitudinal evaluation of bone mass and quality in children and young adults with juvenile onset systemic lupus erythematosus (JSLE): role of bone mass determinants analyzed by DXA, PQCT and QUS. (January 2014) - Stagi, S; Cavalli, L; Bertini, F; Cerinic, M Matucci; Brandi, M Luisa; Falcini, F
Introduction: Stefano Stagi and Loredana Cavalli contributed equally to the manuscript; Maria Luisa Brandi and Fernanda Falcini contributed equally to the manuscript. There are few prospective data on bone mass and quality in patients with juvenile onset systemic lupus erythematosus (JSLE). There are also few studies analyzing bone mass and quality determinants by using at the same time dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT) and quantitative ultrasound (QUS). Objective: The objective of this paper is to evaluate cross-sectionally and longitudinally bone mass and quality determinants in adolescents and young adults with JSLE, and to identify the main predictors of reduced bone mineral density (BMD) and bone quality using these techniques. Methods: Fifty-six patients with JSLE (mean age 18.5 ± 5.7 years) entered the study. In all subjects DXA scan at the lumbar spine, radius pQCT and phalangeal QUS were performed the same day. Of these, 46 patients (mean age 23.1 ± 6.2 years) were revaluated with a second DXA, pQCT and QUS. The data obtained were compared with 72 and 80 age- and sex- matched healthy controls. Results: At the first evaluation, JSLE patients had a reduced spine BMAD SDS ( p  < 0.001), and significantly lower levels of TrabBMD ( p  < 0.0001), SSIp ( p  < 0.05), AD-SoS and QUS z -score ( p  < 0.005) but not reduced muscleCSA and CBA values. CortBMD and FatCSA were significantly increased ( p  < 0.0001). These data were confirmed at longitudinal evaluation regarding spine BMAD SDS ( p  < 0.001), TrabBMD ( p  < 0.0001), FatCSA ( p  < 0.005), AD-SoS ( p  < 0.001), and QUS z -score ( p  < 0.005) but not muscle CSA ( p  ≤ 0.05) and CBA ( p  < 0.0001). SSIp and CortBMD longitudinal evaluation showed that JSLE patients did not present significant differences in comparison to controls. Conclusions: Patients with JSLE have a low bone mass without catch-up growth over time, causing a reduction of peak bone mass with high risk of osteoporosis in early adulthood. To reduce the risk, close monitoring of BMD, better control of disease activity, physical activity and dietary intake of calcium and vitamin D are advocated to ameliorate the loss of bone mass. In patients with proved osteoporosis therapeutic approaches including bisphosphonates should be considered.